MEMBENTUK IMAN ANAK DI ERA DIGITAL: STRATEGI PEMBELAJARAN TEOLOGI YANG RELEVAN BAGI SEKOLAH MINGGU - Sihite, Jelita; Restu Sinta (STT IKSM SANTOSA ASIH, 2025)
The rapid advancement of digital technology has profoundly transformed how children think, behave, learn, and interact with their surroundings. Within the field of Christian faith education—particularly in the context of Sunday School—this transformation presents both challenges and opportunities. Grounded in 2 Timothy 3:14–15 and Mark 10:13–16, this study argues that faith formation must begin early through genuine engagement with Scripture and a personal encounter with Christ. The Apostle Paul emphasizes that faith is rooted in the Scriptures introduced during childhood, while Jesus’ acceptance of children reveals God’s inclusive love and the significance of childlike faith in the Kingdom of God. In the digital era, traditional methods such as memorization and lecturing have become insufficient. Therefore, theological education must be re-envisioned by integrating digital media as a creative, participatory, and contextual means of proclaiming the Gospel. Viewing technology not as a distraction but as a pedagogical partner enables Sunday School to nurture faith, shape character, and deepen children’s relationship with Christ. Ultimately, technology functions not as a threat to faith but as a pastoral and theological instrument that fosters spiritual transformation amid the complexities of the digital age.